Fistula Tract Laser Closure (FiLac) versus Standard Fistulectomy in the Treatment of Simple Perianal Fistula: A Prospective Interventional Study - Shreethi Sasidharan Pillai; D Balaji; Harshwanth Chandhar; G Tilak Ramu; K Shanmugapriya (Journal of Clinical and Diagnostic Research)
Introduction: Perianal fistulas pose significant challenges due to their impact on patient Quality of Life (QoL) and their recurrent nature. Traditional treatments, such as standard fistulectomy, are effective but may lead to complications such as prolonged healing and postoperative pain. Fistula Tract Laser Closure (FiLaC) is a promising alternative that offers minimally invasive benefits. Aim: To compare short-term (postoperative pain, bleeding, mean hospital stay) and intermediate-term (wound healing) outcomes between FiLaC and standard fistulectomy in the treatment of simple perianal fistulas. Materials and Methods: A prospective interventional study was conducted at SRM Medical College Hospital and Research Centre, Chengalpettu, Tamil Nadu, India, in the Department of General Surgery over a period of 18 months, involving 108 patients randomised into FiLaC (group A) and standard fistulectomy (group B). Data on demographics, chief complaints, co-morbidities, short-term (postoperative pain, bleeding, mean hospital stay), and intermediate-term (wound healing) outcomes, as well as postoperative recovery, were collected and compared. Continuous variables were presented as descriptive statistics (mean and standard deviation), and a t-test was applied to determine associations. Categorical variables were expressed as frequency distributions and percentages. The association between categorical variables was tested using Chi-square tests, with a p-value of <0.05 considered statistically significant. Results: A total of 108 patients were involved in the present study. In group A (fistula laser closure), most participants (50%) were aged 20-40 years, while in group B (standard fistulectomy), the majority (46.3%) were aged 41-60 years. In group A (fistula laser closure), 40 (74.1%) were males and 14 (25.9%) were females. In group B (standard fistulectomy), 34 (63%) were males and 20 (37%) were females. group A exhibited shorter average operating times (27.59 vs. 34.8 minutes, p<0.001), reduced mean hospital stays (5 vs. 7 days, p<0.001), and faster wound healing. Postoperatively, FiLaC patients reported lower pain scores (p<0.001) and experienced less blood loss (p<0.001) compared to those who underwent standard fistulectomy. Moreover, FiLaC demonstrated a lower recurrence rate (9.3 vs. 25.6%, p=0.023), highlighting its efficacy in preventing fistula recurrence. Conclusion: FiLaC demonstrates advantages over standard fistulectomy in terms of efficiency, recovery time, and complication rates for treating simple perianal fistulas. Further research involving larger cohorts is warranted to validate these findings.